2021
DOI: 10.1093/humrep/deab126.059
|View full text |Cite
|
Sign up to set email alerts
|

O-134 Cochrane review on the effect of pentoxifylline for endometriosis

Abstract: Study question To assess the effect of pentoxifylline, a methyl-xanthine with anti-inflammatory effects, for the management of premenopausal women with endometriosis. Summary answer There is not enough evidence to support the use of pentoxifylline in the management of premenopausal women with endometriosis to improve fertility and pain outcomes. What is known already … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…3.12±1.42 cm in metformin alone, p=0.012s) aligns with the broader narrative in endometriosis management, where combination therapies often outperform single-agent treatments, as suggested by Taniguchi et al 25 However, the non-significant differences in VAS score and IL-6 levels post-treatment (VAS: p=0.188ns, IL-6: p=0.147ns) present a more nuanced picture, indicative of the multifaceted nature of endometriosis symptomatology and its management, resonating with findings by Grammatis et al 26 The pregnancy rates observed in our study, 8% in the pentoxifylline plus metformin group versus 3.85% in the metformin alone group, did not show a significant difference (p=0.610ns). This finding is in line with Balasch et al and Gardezi et al where treatment modalities did not significantly impact fertility outcomes.…”
Section: Discussionsupporting
confidence: 63%
“…3.12±1.42 cm in metformin alone, p=0.012s) aligns with the broader narrative in endometriosis management, where combination therapies often outperform single-agent treatments, as suggested by Taniguchi et al 25 However, the non-significant differences in VAS score and IL-6 levels post-treatment (VAS: p=0.188ns, IL-6: p=0.147ns) present a more nuanced picture, indicative of the multifaceted nature of endometriosis symptomatology and its management, resonating with findings by Grammatis et al 26 The pregnancy rates observed in our study, 8% in the pentoxifylline plus metformin group versus 3.85% in the metformin alone group, did not show a significant difference (p=0.610ns). This finding is in line with Balasch et al and Gardezi et al where treatment modalities did not significantly impact fertility outcomes.…”
Section: Discussionsupporting
confidence: 63%
“…PDE4B is mainly present in immune and epithelial cells and has a role modulating inflammation and epithelial integrity. 83 Considering current evidence for Pentoxifylline, which was used to treat endometriosis by targeting PDE4B encoded protein, 53 this study provides some evidence for the further investigation of PDE4B for the purpose of treating both endometriosis and GI disorders.…”
Section: Discussionmentioning
confidence: 84%
“…Compared with IBS, which has multiple sources of evidence to support the promising treatment effect of Pentoxifylline, 51 , 52 there is limited evidence on whether Pentoxifylline impacts endometriosis related pain reduction. 53 …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the involvement of gastrin and CCKBR in estrogen metabolism may implicate this gene as a potential drug target for endometriosis. Moreover, considering the low quality of current evidence for Pentoxifylline which was used to treat endometriosis by targeting PDE4B encoded protein 53 , this study provides more evidence and novel insight for the further investigation of PDE4B for the purpose of treating both endometriosis and GI disorders.…”
Section: Evidence For the Potential Of Drug Repositioning In Clinicsmentioning
confidence: 99%
“…In addition, PDE4B with its encoded protein cAMP-specific 3',5'-cyclic phosphodiesterase 4B being targeted by Pentoxifylline, acts as an inhibitor targeting the immune system and has been clinically trialled for the treatment of both endometriosis (phase III) and IBS (Phase IV) separately (Table 6). Compared with IBS which has multiple sources of evidence to support the promising treatment effect of Pentoxifylline 51 52 , there is limited evidence on whether Pentoxifylline impacts endometriosis related pain reduction 53 . Notably, when not restricted to the aforementioned gene set, 34 genes with encoded proteins were targets of both endometriosis and IBS/GORD/PUD drugs (Supplementary Table 13).…”
Section: Potential For Drug Repositioningmentioning
confidence: 99%